Anti-diabetic action of Lupinus angustifolius seed proteins and peptides - Tapadia, Mrunmai (Curtin University, 2019)
Lupin seed proteins have been reported to exhibit hypoglycaemic action in animals and humans. This research focuses on exploring in-vitro anti-diabetic action of proteins extracted from Lupinus angustifolius seed. A novel insulin secretory mechanism of extract hydrolysate mediating through Gaq protein signalling pathway in pancreatic ß-cells was established. γ-conglutin protein, a glucose modulating agent, was separated from the extract. Purified γ-conglutin was characterised and hydrolysed to evaluate its anti-diabetic properties in pancreatic ß-cells and myotubes.